The decapitation of Slovenia's Catholic Church: social factors and consequences. Issue 2 (2nd April 2016) - Smrke, Marjan
ABSTRACT: This article discusses the financial collapse of Slovenia's Catholic Church, a scandal which resulted in the deposition of the country's archbishops, and its impact on religious belief and on the relations within the Slovenian Catholic establishment and community. Trust in the Church and religious participation have dropped markedly in Slovenia over recent years. While there are no significant changes in religious belief, other religious indicators continue to reflect an ongoing moderate trend towards secularisation that is characteristic of Slovenia in the post-socialist era. The public discourse of the Church's leadership and lay Catholics reveals tensions on the reasons behind the fall of the Church's financial empire and on the question of responsibility in the removal of Slovenia's archbishops. Two general types of reactions were identified in a content analysis of texts from a five-month period after the last depositions. Views within the Slovene Catholic Church, which uphold the institution's traditional stance, tend to explain these developments as part of a conspiracy against the Church. Others that are more open and reflective are critical towards the actions of the Church and demand change from within the institution.